Volumetric Body Mass Estimate and in vivo Reconstruction of the Russian Pareiasaur Scutosaurus karpinskii - Romano, Marco; Manucci, Fabio; Rubidge, Bruce; Van den Brandt, Marc J. (Frontiers in Ecology and Evolution, 2021)
Pareiasaurs (Amniota, Parareptilia) were characterized by a global distribution during the Permian period, forming an important component of middle (Capitanian) and late Permian (Lopingian) terrestrial tetrapod biodiversity. This clade represents an early evolution of sizes over a ton, playing a fundamental role in the structure of middle and late Permian biodiversity and ecosystems. Despite their important ecological role and relative abundance around the world, our general knowledge of the biology of these extinct tetrapods is still quite limited. In this contribution we provide a possible in vivo reconstruction of the largest individual of the species Scutosaurus karpinskii and a volumetric body mass estimate for the taxon, considering that body size is one of the most important biological aspects of organisms. The body mass of Scutosaurus was calculated using a 3D photogrammetric model of the complete mounted skeleton PIN 2005/1537 from the Sokolki locality, Arkhangelsk Region, Russia, on exhibit at the Borissiak Paleontological Institute, Russian Academy of Sciences (Moscow). By applying three different densities for living tissues of 0.99, 1, and 1.15 kg/1,000 cm3 to reconstructed “slim,” “average” and “fat” 3D models we obtain average body masses, respectively, of 1,060, 1,160, and 1,330 kg, with a total range varying from a minimum of one ton to a maximum of 1.46 tons. Choosing the average model as the most plausible reconstruction and close to the natural condition, we consider a body mass estimate of 1,160 kg as the most robust value for Scutosaurus, a value compatible with that of a large terrestrial adult black rhino and domestic cow. This contribution demonstrates that barrel-shaped herbivores, subsisting on a high-fiber diet and with a body mass exceeding a ton, had already evolved in the upper Palaeozoic among parareptiles, shedding new light on the structure of the first modern terrestrial ecosystems.